2013
DOI: 10.1016/j.celrep.2013.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeting of JAK2 and Bcl-2/Bcl-xL to Cure Mutant JAK2-Driven Malignancies and Overcome Acquired Resistance to JAK2 Inhibitors

Abstract: SummaryTo design rational therapies for JAK2-driven hematological malignancies, we functionally dissected the key survival pathways downstream of hyperactive JAK2. In tumors driven by mutant JAK2, Stat1, Stat3, Stat5, and the Pi3k and Mek/Erk pathways were constitutively active, and gene expression profiling of TEL-JAK2 T-ALL cells revealed the upregulation of prosurvival Bcl-2 family genes. Combining the Bcl-2/Bcl-xL inhibitor ABT-737 with JAK2 inhibitors mediated prolonged disease regressions and cures in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
101
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 41 publications
9
101
0
6
Order By: Relevance
“…Navitoclax, a Bcl-2/Bcl-xL inhibitor, was identified as the most promising candidate for multicomponent therapy. It was recently reported that apoptosis induced by JAK2 inhibition was enhanced by the Bcl-2/Bcl-xL inhibitor ABT-737 in mutant JAK2-driven malignancies (20,21). We demonstrated that the combination of ruxolitinib and navitoclax showed additive/synergistic efficacy inhibiting proliferation of IL-2-dependent ATL cell lines and synergy prolonging survival in a murine model of human ATL.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Navitoclax, a Bcl-2/Bcl-xL inhibitor, was identified as the most promising candidate for multicomponent therapy. It was recently reported that apoptosis induced by JAK2 inhibition was enhanced by the Bcl-2/Bcl-xL inhibitor ABT-737 in mutant JAK2-driven malignancies (20,21). We demonstrated that the combination of ruxolitinib and navitoclax showed additive/synergistic efficacy inhibiting proliferation of IL-2-dependent ATL cell lines and synergy prolonging survival in a murine model of human ATL.…”
mentioning
confidence: 72%
“…Consequently, caspase 3/7 activation and an associated increase in PARP and Mcl-1 cleavage occurred upon cotreatment with ruxolitinib and navatoclax. Aspects of these results have been noted in other disorders (13,20,21,36). Gozgit et al reported that inhibition of JAK2 blocked production of the Pim1/2 kinases and resulted in a corresponding decrease in BAD phosphorylation (13), and Will et al demonstrated that apoptosis induced by JAK2 inhibition is mediated by Bim and enhanced by the BH3 mimetic ABT-737 in JAK2 mutant human erythroid cells (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations